Robust Time-Frequency Distributions with Complex-Lag Argument - Žarić Nikola; Orović Irena; Stanković Srdjan (EURASIP Journal on Advances in Signal Processing, 2010)
The robust time-frequency distributions with complex-lag argument are proposed. They can provide an accurate estimation of fast varying instantaneous frequency in the presence of noise with heavy-tailed probability density function. The L-estimate form of this distribution is defined and it includes the L-estimate form of Wigner distribution as a special case. A modification for multicomponent signal representation is proposed, as well. Theoretical considerations are illustrated by the examples.